Questioning Strategies in English Literature Lectures in an Indonesian University - Akhyar Rido; Heri Kuswoyo; Sandi Nuansa (Lingua Cultura, 2020)
The research aimed to investigate the questioning strategies used by lecturers in English literature lectures an Indonesian university and how they were manifested. Applying the qualitative approach and Rido, Ibrahim, and Nambiar’s conceptual framework in 2015, the research analyzed three lectures of English literature consisting of prose, literary criticism, and drama. Data were collected through 300 minutes of video-recordings. The findings reveal that the lecturers employ various types of questions such as display, referential, follow-up, and rhetorical questions. The lecturers manifest the questions by rephrasing questions first, then nominating students, asking questions to the entire class, encouraging students to initiate questions, and moving closer to students when asking questions. The questioning strategies help the lecturers to lead the discussion, check students’ understanding, offer the students to share ideas, and improve students’ participation. As a result, the students become active in expressing thoughts, sharing ideas, and even initiating questions. The research can be a guideline for lecturers to create meaningful and interactive lectures to produce competent and critical students.